Efektivitas Relaksasi Otot Progesif Terhadap Kualitas Tidur Keluarga Pasien di Ruang ICU - Heldawati Heldawati; Tina Handayani Nasution; Devi Rahmayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Sleep quality is a person's level of satisfaction with their sleep. Poor sleep quality is a decrease in sleep quality which can be seen from frequently woke up dured sleep at night and had difficulty fell asleep. A person who lacks sleep can cause physical and psychological health to decline. Progressive muscle relaxation is a non-pharmacological therapy that can improve sleep quality Purpose: This research aims to determine the effectiveness of progressive muscle relaxation on the sleep quality of patient families in the ICU room Methods: This study uses a Quasi-experiment one group pretest posttest design with consecutive sampling technique on 30 families of patients in the ICU waited room used the RCSQ questionnaire. Bivariate analysis used the Wilcoxon test. Result: Data analysis shows the sig value. 0.000 (p > 0.05) so Ho is rejected, means that there is an effect of progressive muscle relaxation on the sleep quality of the patient's family in the ICU room at Ulin Hospital, Banjarmasin Result: The sleep quality of the patient's family before the intervention was 30 respondents who experienced poor sleep quality and after the intervention 30 respondents experienced good sleep quality. So this therapy can be used to improve the quality of family sleep Implication: There is the effectiveness of progressive muscle relaxation on the sleep quality of patient families in the ICU Room